1988
DOI: 10.1084/jem.167.4.1350
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of helper/inducer T lymphocytes. II. Effects of interleukin 4- and interleukin 2-producing T cell clones on resting B lymphocytes.

Abstract: To compare the helper function of murine T cell clones that secrete IL-2 and IFN-gamma (Th1 cells) or IL-4 and IL-5 (Th2), purified resting B cells were stimulated with F(ab')2 rabbit anti-mouse Ig (RAMG) and rabbit Ig-specific, class II MHC-restricted cloned T cells belonging to the two subsets. Both Th2 clones examined induced strong proliferative responses of B cells in the presence of RAMG, as well as the secretion of IgM and IgG1 antibodies. In contrast, the Th1 clones tested failed to stimulate B cell gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(60 citation statements)
references
References 27 publications
6
54
0
Order By: Relevance
“…Although early in vitro studies indicated that both Th1 and Th2 cells could support B cell responses (15)(16)(17), the capacity of Th1 cells to provide cognate help for B cells is controversial, with some studies reporting that they are relatively deficient in this function (21,39,40). However, care must be taken when interpreting such in vitro studies, as examination of several Th1 and Th2 clones revealed considerable variation in their ability to help B cells with some Th2 clones failing to support Ab synthesis at all (15).…”
Section: Discussionmentioning
confidence: 99%
“…Although early in vitro studies indicated that both Th1 and Th2 cells could support B cell responses (15)(16)(17), the capacity of Th1 cells to provide cognate help for B cells is controversial, with some studies reporting that they are relatively deficient in this function (21,39,40). However, care must be taken when interpreting such in vitro studies, as examination of several Th1 and Th2 clones revealed considerable variation in their ability to help B cells with some Th2 clones failing to support Ab synthesis at all (15).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, IL-4, IL-6, and interferon-y (IFNy) may be important lymphokines. It is known that IL-4 plays a role in immunoglobulin isotype switching (27), and that it can inhibit IgM secretion in vitro (28). IL-6, which was found at high levels only in the arthritic monkeys, is a cytokine that, in vivo, can induce polyclonal B cell activation and autoantibody production (29).…”
Section: Wfmentioning
confidence: 99%
“…A similarly balanced IgG1: IgG2a ratio was observed following delivery of OVA and CpG DNA (0.5). These results suggest that VRP co-delivery significantly alters the systemic IgG subtype profile compared to delivery of antigen alone, and results in a balanced antibody response with the production of both Th1 and Th2 IgG antibodies [34,35]. The antibody adjuvant data presented here and in Thompson et al [29] were derived from experiments performed in Balb/c mice; however, we have observed significant antibody adjuvant activity in several mouse strains including Balb/c, C57BL/6, and 129 Sv/Ev, suggesting that the VRP adjuvant effect is not dependent upon a specific mouse genotype (Thompson J.M.…”
Section: Vrp Adjuvants Promote a Balanced Th1/th2 Antibody Profilementioning
confidence: 99%